Evaluation of clinical, biohumoral, and morphological findings of the thyroid gland as possible predictors of risk for cancer in patients with atoxic nodular and multinodular goiter - Malović, Dragana; Dragović, Tamara; Kiković, Saša; Ristić, Petar; D. Marinković, Dejan; Djuran, Zorana; Kuzmić-Janković, Snežana; Jovanović, Stevan; Rakočević, Jelena; Hajduković, Zoran (Vojnosanitetski pregled, 2024)
Background/Aim. Thyroid nodules are usually asymptomatic and may occur in 68% of the general population. In most cases, they are discovered incidentally. As malignancy is proven in 10–15% of cases, a rational diagnostic approach is necessary. The aim of this retrospective study was to examine and grade different characteristics of patients with nodular and multinodular atoxic goiter in order to identify the potential predictors for the assessment of thyroid cancer risk. Methods. The study included 275 patients with nodular and multinodular atoxic goiter hospitalized at the Clinic for Endocrinology of the Military Medical Academy, Belgrade, Serbia, from January 1, 2017, to October 1, 2022, for preoperative preparation. The most relevant clinical, biohumoral, and pathomorphological characteristics were analyzed. Results. Patients with multiple thyroid nodules were older (57.21 ± 13.16 vs. 49.36 ± 15.83 years, p < 0.001) and had higher body mass index (29.12 kg/m2 vs. 26.50 kg/m2, p = 0.004) compared to patients with one nodule. On the other hand, patients with one thyroid nodule had a higher level of the thyroid-stimulating hormone than patients with multiple nodules (1.73 mIU/L vs. 1.21 mIU/L, p
Keywords: biopsy, fine needle; goiter; neoplasm staging; thyroid neoplasms; thyroid nodule.